2005
DOI: 10.1016/j.clim.2005.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Increase of activated T-cells and up-regulation of Smad7 without elevation of TGF-beta expression in tonsils from patients with pustulosis palmaris et plantaris

Abstract: SUMMARYPustulosis palmaris et plantaris (PPP) is known to be skin disease related to tonsillitis, because the pustulosis often become exacerbated during acute tonsillitis and disappears after tonsillectomy. However, etiology of PPP remains unclear. In this study, we investigated the activation of tonsillar T-cell from PPP patients. Furthermore, we analyzed expressions of cytotoxic T-lymphocyte antigen-4 (CTLA4) that is a co-stimulatory molecule for inhibition of T-cell activation and of Smad7 that is a regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Recent studies have demonstrated that Smad7 expression is induced by TGF-b, EGF and the inflammatory cytokines, such as TNF-a and IFN-g (Afrakhte et al, 1998;Takahara et al, 2005). Upregulation of Smad7 may induce cell proliferation through the inhibition of p21…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that Smad7 expression is induced by TGF-b, EGF and the inflammatory cytokines, such as TNF-a and IFN-g (Afrakhte et al, 1998;Takahara et al, 2005). Upregulation of Smad7 may induce cell proliferation through the inhibition of p21…”
Section: Discussionmentioning
confidence: 99%
“…Takahara et al published a case series reporting an improvement in skin lesions in 87% of PPP patients (n = 47) at 12 months following tonsillectomy (10) (Table 1). The group then reported a prospective case series of 116 patients undergoing tonsillectomy for the treatment of PPP (11).…”
Section: Resultsmentioning
confidence: 99%
“…Tonsillar T cells in PPP patients were supposed to exhibit higher levels of activity and proliferation. We determined through quantitative immunohistological analysis that T‐cell nodules on tonsillar tissues of PPP patients were more expanded; additionally, there was a positive correlation between the enlargement and clinical improvement of skin lesions after tonsillectomy. Kawaguchi et al .…”
Section: Pathogenic Role Of Tonsils In Pppmentioning
confidence: 99%